Osnove turističnega vodenja: Učbenik - Rajner, Igor; Gorenak, Mitja (University of Maribor Press, 2022)
The textbook Introduction to tour guiding presents a collection of five chapters in which students are introduced to several practical approaches to tour guiding. The first chapter focuses on the preparation of the itinerary, using a technical approach to divide the program of the tour that is rich in words into a logistical solution suitable for a tour guide. The second chapter focuses on the preparation of materials, where the emphasis is on the correct approach to finding relevant literature. Since data alone is not enough, we can added the third chapter, where we create stories from the data, which are very important for tourism. The fourth chapter presents support materials for tour guides that enrich the travel experience of passengers. The last fifth chapter completes the whole, as it adds an insight into many situations that cannot be predicted, but it is precisely in these that the tour guide must prove himself all the more. The entire textbook is designed in such a way that the content is strongly interwoven with numerous exercises and examples that will enable students to gain an in-depth understanding of the selected content.